Співпраця держави та бізнесу у зовнішньоекономічних проєктах - Угольков, Є. О.; Угольков, А. О.; Ugolkov, I.; Ugolkov, A. (Видавництво Львівської політехніки, 2024)
Досліджено сучасні практики та цілі співпраці держави та бізнесу в зовнішньоекономічних проєктах. Глобалізація та взаємозалежність економік створюють певні виклики для розвитку країн. Співпраця між державним та приватним секторами надзвичайно важлива для досягнення успіху в міжнародних проєктах. У статті розглянуто найкращі практики такої співпраці, зокрема розвиток інфраструктури, модернізацію транспортної галузі, покращення туристичної сфери обслуговування та створення сприятливого бізнес-середовища. Висвітлено ключові цілі та принципи співпраці. Крім того, проаналізовано стратегії керування ризиками та використання сучасних засобів управління проєк-тами для забезпечення їх успішного виконання.

Purpose. The purpose of this article is to identify and analyze the key aspects of cooperation between the state and business in foreign economic projects, analyze risk management strategies, and identify tools of effective project management. Design/methodology/approach. The research employed the following universal scientific methods of cognition: analysis and synthesis, organization, identification of differences, and interpretation. The foundation of the research was made up of scientific works and articles published on the internet, belonging to well-known Ukrainian and international scientists. These sources were carefully selected to ensure a reliable informational, theoretical, and methodological base. They cover a wide range of issues related to the interaction between the state and business in the field of foreign economic activity, including the analysis of successful foreign practices and their potential application in the Ukrainian context. Findings. This article examines current practices and strategies of cooperation between the state and business in foreign economic projects. Cooperation between the public and private sectors is extremely important for achieving success in international projects. Understanding the goals and interests of both parties is one of the key areas of successful cooperation. The state is interested in promoting national interests, supporting the country’s economic growth in the international arena, and attracting foreign investment. Business, for its part, seeks to maximize profits and expand its markets. Therefore, it is important that both sides clearly understand and define their goals and find common points of cooperation. The article analyzes the goals of the government and business in implementing foreign economic projects. One of the state’s goals in such projects is to actively promote the country's economic development by attracting foreign investment, developing trade and infrastructure. In the context of martial law in Ukraine, the state’s priority goal is to ensure national security. Participation in foreign economic projects can be an effective way to increase international prestige. Practical implications. Increasing sales volumes and maximizing profits in foreign economic projects is one of the key business goals. Expanding sales markets, introducing the latest technologies and marketing tools, as well as raising awareness of products or services on the international market help to achieve this goal. One of the key goals of business in foreign economic projects is also risk differentiation. This strategy is to distribute investments and business activities between different areas or regions in order to reduce the overall risk of losses. The analyze of risk management strategies and identifying effective project management tools is important to ensure their successful implementation. One of the important areas of cooperation between the state and business in foreign economic projects is effective risk management. To successfully manage these risks, it is necessary to establish effective mechanisms for monitoring, assessing and managing risks at various stages of the project. The article analyze the best practices of such cooperation, including infrastructure development, modernization of the transportation gas industry, improvement of tourist services, and creation of a favorable business environment. The key principles of cooperation, such as interaction between different stakeholders, transparency and effective management, are highlighted. From a practical standpoint, this research offers valuable insights and guidelines to both the government and businesses on how to effectively collaborate and manage joint projects. Originality/value. The research conducted in this article identifies the main areas of interaction between the state and business in foreign economic projects. Effective risk management strategies for both the state and business are identified. The use of modern project management tools, such as the latest software methods, cloud services, management methodologies and communication platforms, contributes to the effective realization of the goals of the state and business.
State and business cooperation in foreign economic projects
Keywords: партнерство; державний сектор; приватний сектор; зовнішньоекономічна діяльність; partnership; public sector; private sector; foreign economic activity; F13; I30; О19; 339.542.6